Neuroprotective Effects of Astaxanthin in a Scopolamine-Induced Rat Model of Alzheimer’S Disease Through Antioxidant/Anti-Inflammatory Pathways and Opioid/Benzodiazepine Receptors: Attenuation of nrf2 Nf-Κb, and Interconnected Pathways - Echeverria-Morgado, J (Frontiers Media SA, 2025)
Background: Given the complexity of pathological mechanisms behind Alzheimer’s disease (AD), there is a pressing need for novel multi-targeting therapeutic agents. Astaxanthin, a natural compound with diverse biological effects, has emerged as a potential candidate in neuronal diseases. Purpose: This study aimed to evaluate the neuroprotective effects of astaxanthin in a scopolamine-induced rat model of AD. Materials and methods: In total, 36 male Wistar rats were divided into six groups, including a control group receiving normal saline, a negative control group treated with scopolamine (1 mg/kg), and two groups receiving astaxanthin at doses of 5 and 10 mg/kg. Additionally, two groups were pre-treated with naloxone (0.1 mg/kg) or flumazenil (0.5 mg/kg) to block opioid and benzodiazepine receptors, respectively, followed by receiving the most effective dose of astaxanthin (i.e., 10 mg/kg). Treatments were administered via intraperitoneal injection for 14 consecutive days and behavioral tests were done. Biochemical analyses, zymography, Western blotting, and histopathological examinations were also performed. Results and discussion: Astaxanthin treatment significantly improved cognitive function, enhanced plasma antioxidant capacity by increasing catalase and glutathione levels, and reduced nitrite levels. It also increased serum activity of matrix metalloproteinase 2 (MMP-2), while decreasing MMP-9, increasing the expression of nuclear factor erythroid 2–related factor 2 (Nrf-2) and decreasing nuclear factor kappa B (NF-κB) in hippocampal tissue. Histopathological findings indicated reduced hippocampal damage after astaxanthin administration. The aforementioned protective effects of astaxanthin were reversed by naloxone and flumazenil. Conclusion: Astaxanthin demonstrates protective effects against scopolamine-induced AD through its neuroprotective, antioxidant, and anti-inflammatory properties, potentially involving interactions with opioid and benzodiazepine receptors. © © 2025 Rastinpour, Fakhri, Abbaszadeh, Ranjbari, Kiani, Namiq Amin and Echeverría.